1968
DOI: 10.1128/aem.16.6.819-821.1968
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Reported Aflatoxin Production by Fungi Outside the Aspergillus flavus Group

Abstract: A screening study of 121 fungus isolates, representing 29 species, for aflatoxin synthesis demonstrated this property only in Aspergillus flavus and A. parasiticus. Eight of the organisms found negative were isolates reported by other investigators to produce aflatoxin. Since similar negative reports have come from several other workers, it is concluded that only the A. flavus group of Aspergillus can presently be certified as sources of these toxins. Reasons for possible false-positive findings are discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
1

Year Published

1969
1969
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 8 publications
2
7
1
Order By: Relevance
“…Of all the samples tested, only the corn held at 35 C and 26% moisture contained aflatoxin G1; all others contained only aflatoxins B1 and B2. In the rewet corn, higher aflatoxin levels were found at 30 and 35 C than at 24 C. This optimal temperature range (30 to 35 C) was somewhat higher than that found by Schindler et al (21), who obtained best production of aflatoxins between 25 and 35 C. These workers also demonstrated toxin production at 13 C; however, we were unable to detect aflatoxins in corn incubated at this temperature. This is most readily explained by the natural competition between the mycoflora in our samples, whereas Schindler et al used inocu-lated substrate.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…Of all the samples tested, only the corn held at 35 C and 26% moisture contained aflatoxin G1; all others contained only aflatoxins B1 and B2. In the rewet corn, higher aflatoxin levels were found at 30 and 35 C than at 24 C. This optimal temperature range (30 to 35 C) was somewhat higher than that found by Schindler et al (21), who obtained best production of aflatoxins between 25 and 35 C. These workers also demonstrated toxin production at 13 C; however, we were unable to detect aflatoxins in corn incubated at this temperature. This is most readily explained by the natural competition between the mycoflora in our samples, whereas Schindler et al used inocu-lated substrate.…”
Section: Resultscontrasting
confidence: 78%
“…High levels of aflatoxin (greater than 250 ng/g) have occurred in some batches of peanut and cottonseed meals (9). The problem of control of aflatoxin production in foodstuffs has been compounded by the implication of other aspergilli and penicillia as aflatoxin producers (7,10,11,22), although these results have recently been questioned (15,25).…”
mentioning
confidence: 99%
“…Likewise, Parrish et al, (1966), found that no aflatoxins were produced by 45 strains of Aspergillus (which were not members of the A. flavus group) and 10 strains of Pénicillium. The findings presented here support those of Wilson et (1968) and Parrish et al (1966) that fungi from other than the A, flavus group are not likely to produce aflatoxins. However, owing to the extreme toxicity of the aflatoxins and the very versatile metabolic nature of the fungi, it may be regarded as still questionable Chloroform;acetone (9:1) .…”
Section: Screening Of Mold Isolates For Aflatoxin Productionsupporting
confidence: 86%
“…
Aflatoxins are toxic metabolites of Aspergillus flavus and Aspergillus parasiticus (12). They are important for human beings because of their carcinogenic properties (1 3).
…”
mentioning
confidence: 99%